Oxytocin Massage Can Increase Breastfeeding Production in Postpartum Mothers - Epti Yorita; Sri Yanniarti; Istiarika Istiarika (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Breastfeeding is the most appropriate feeding method for babies, so the Government issued a policy of Implementing 10 Steps to Successful Breastfeeding to support successful breastfeeding. However, the coverage of exclusive breastfeeding is still low. Pre-lacteal feeding, culture, and common knowledge are the causes of the failure of exclusive breastfeeding. In addition, the mother's perception of insufficient milk supply is the most common reason for stopping breastfeeding. Therefore, an oxytocin massage intervention is needed to increase milk production. This study aims to determine the effect of oxytocin massage on breastfeeding production in postpartum mothers in the work area of the Bengkulu City Health Center. Quasi-experimental research design with control group post-test only. The treatment group was postpartum women who were given oxytocin massage, while the control group was given endorphin massage. A sample of 34 people was taken by purposive sampling technique. Data was collected through questionnaires and observation sheets. A breast pump measures breastfeeding production. Data were analyzed univariately, bivariate with independent t-test, and multivariate with Ancona. The results showed that there was an effect of oxytocin massage on milk production p=0.00. The mean difference was 1.54. There is an effect of IMD status on breast milk production p=0.00, and there is an effect of frequency of breastfeeding on milk production p=0.00. Oxytocin massage is not the most dominant variable affecting breastfeeding production. It is recommended that health service providers provide breastfeeding education continuously during pregnancy, perinatal, and until the baby is two years old by involving the family and using digital information technology that can reach all targets. Keywords: Oxytocin massage, Breastfeeding Production